A new pattern to quantitatively evaluate the value of ecosystem services in the large-scale open-pit coal mining area - Shi, Jieqing; Li, Dengao; Shen, Chaoyong; Yang, Jing; Wu, Fanming (Frontiers in Ecology and Evolution, 2023)
Open-pit coal mining could disrupt the ecosystems and lead to the loss of service values for the ecosystem either through direct occupation or indirect impacts on adjacent ecosystems. In this research, we monitored and quantified the value of ecosystem services in the large-scale open-pit coal mining area by a new accounting system - Gross Ecosystem Product (GEP). Specifically, based on the diverse spatial and non-spatial data, the GEP dataset was established from the spatial and temporal dimensions. And the exploratory spatial data analyses were utilized to explore the spatio-temporal characteristics of the GEP. The driving factors for the changes and spatial heterogeneity of the GEP were investigated with the assistance of statistical approach and interpretable models in machine learning. Finally, the win-win situation for both the economy and ecosystem in our study area was confirmed by restricting the growth areas of the mining. The results indicated that: (i) The GEP grew from 3.34 billion CNY in 1990 to 46.67 billion CNY in 2020, accompanied by the average annual growth rates of GEP decreased from 30.78% between 1990 to 1995 to 9.1% between 2015 to 2020 in the study area;(ii) The classified GEP further indicated that the proportions with high grades(Level 4-6) of GEP decreased from 51.90% in 1990 to 32.18% in 2020;(iii) The GEP possessed the spatial correlation and the negative spatial correlations were existence in the mining areas with the high significances; the mining areas were also spatially consistent with the domains of the high-density and hot-spot variation of GEP;(iv) The mining effects, human activity intensity and GDP all played salient roles in the spatial heterogeneity and spatio-temporal dynamics of the GEP;(v) When the annual growth rate of mining areas is limited between 4.56% and 5.03%, the value of GEP in 2020 will be 1.04~1.1 times higher than the existing one. This research introduces a new pattern for the ecosystem services in the large-scale open-pit coal mining area, and verifies the feasibility of this system. And the accounting results and their analyses will contribute to the future regional sustainable development and ecosystem management in the open-pit coal mining areas.